Metabolic Effects of a Stabilizing Peptide Fusion Protein of Leptin in Normal Mice - Park, H.; Lee, S.-B.; Koh, J.; Kim, J. (Hormone and Metabolic Research, 2012)
Leptin is a protein hormone produced by adipocytes. It is secreted into the blood stream and plays a key role in regulating body energy homeostasis by inhibiting feeding behavior followed by decreased body weight. Because protein aggregation is a major problem in therapeutic proteins, we previously demonstrated that a stabilizing peptide (SP) fusion protein of leptin (SP-leptin) appeared to resist aggregation induced by agitation, freezing/thawing, or heat stress. In this study, we fused mouse leptin with the stabilizing peptide and compared the biological activities of leptin and SP-leptin in vivo using a male C57Bl mouse model and ex vivo using MCF7 breast cancer cell lines. Each group of mice was treated with saline, leptin, and SP-leptin for 20 days and the differences in body weight, food intake, abdominal fat contents, and TG concentration were measured. The SP-leptin appeared to decrease the body weight and food intake in male C57Bl mice more significantly than wild type leptin, and the SP-leptin treated MCF7 cells displayed better cell proliferation than leptin. As a consequence of decreased body weight, the SP-leptin treated mouse group showed decreased abdominal fat contents and low triglyceride (TG) concentration. Moreover, the SP-leptin treated mouse group had fewer lipid droplets in liver and reduced lipid droplet size when analyzed by Oil red O and H & E staining. These results demonstrated that SP-leptin is more effective than wild type leptin in normal mice in lowering their body weight and fat contents in the abdominal region, the serum, and the liver.
Keywords: leptin; protein stability; stabilizing peptide; fusion protein; animal experiment; bioefficacy